Metal ion-doped sol-gel film for emulating synaptic activity and short-term non-volatile memory - Nych, Khrystyna; Baek, Eunhye; Baek, Chang Ki; Ibarlucea, Bergoi; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni) (2019 26th IEEE International Conference on Electronics, Circuits and Systems, ICECS 2019, 2019)
We propose a hybrid device substituting the software synapse in artificial neural networks with an individual hardware transistor unit. The unit merges a silicon nanowire semiconductor channel with a metal-ion doped sol-gel film as hybrid gate of the transistor. The film, amorphous and transparent, shows a memristive property due to ion redistribution under bias, emulating synaptic plasticity with pulsed gate stimulation.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Non-volatile memory; Silicon nanowire-based field-effect transistor; Sol-gel